Hospital-acquired SARS-CoV-2 pneumonia in a person living with HIV - Chiappe Gonzalez, Alfredo Juan (Int J STD AIDS, 2020)
We report the case of a 38 year-old man living with well-controlled HIV on antiretroviral therapy who developed cerebellar symptoms and was admitted to hospital for management of an intraventricular cryptococcoma. During his hospital stay he contracted SARS CoV-2 infection within the hospital setting with a fatal outcome.